Design of a Helical-Stabilized, Cyclic, and Nontoxic Analogue of the Peptide Cm-p5 with Improved Antifungal Activity - Vicente, Fidel E. Morales; González-Garcia, Melaine; Diaz Pico, Erbio; Moreno-Castillo, Elena; Garay, Hilda E.; Rosi, Pablo E.; Jimenez, Asiel Mena; Campos-Delgado, Jose A.; Rivera, Daniel G.; Chinea, Glay; Pietro, Rosemeire C. L. R. [UNESP]; Stenger, Steffen; et al. (American Chemical Society (ACS), 2019)
Following the information obtained by a rational design study, a cyclic and helical-stabilized analogue of the peptide Cm-p5 was synthetized. The cyclic monomer showed an increased activity in vitro against Candida albicans and Candida parapsilosis, compared to Cm-p5. Initially, 14 mutants of Cm-p5 were synthesized following a rational design to improve the antifungal activity and pharmacological properties. Antimicrobial testing showed that the activity was lost in each of these 14 analogues, suggesting, as a main conclusion, that a Glu-His salt bridge could stabilize Cm-p5 helical conformation during the interaction with the plasma membrane. A derivative, obtained by substitution of Glu and His for Cys, was synthesized and oxidized with the generation of a cyclic monomer with improved antifungal activity. In addition, two dimers were generated during the oxidation procedure, a parallel and antiparallel one. The dimers showed a helical secondary structure in water, whereas the cyclic monomer only showed this conformation in SDS. Molecular dynamic simulations confirmed the helical stabilizations for all of them, therefore indicating the possible essential role of the Glu-His salt bridge. In addition, the antiparallel dimer showed a moderate activity against Pseudomonas aeruginosa and a significant activity against Listeria monocytogenes. Neither the cyclic monomer nor the dimers were toxic against macrophages or THP-1 human cells. Due to its increased capacity for fungal control compared to fluconazole, its low cytotoxicity, together with a stabilized α-helix and disulfide bridges, that may advance its metabolic stability, and in vivo activity, the new cyclic Cm-p5 monomer represents a potential systemic antifungal therapeutic candidate.